PENGARUH FLEXIBLE WORKING ARRANGEMENT, EMPLOYE ENGAGEMENT, DAN EMOTIONAL INTELLIGENCE TERHADAP EMPLOYE LOYALTY PT SURYACITRA ADIKUSUMA SURABAYA - Yeriko Felis Samudra; Ika Korika Swasti (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to know the influence of Flexible Working Arrangement, Employe Engagement, and Emotional Intelligence to Employe Loyalty PT Suryacitra Adikusuma. This research used quantitative method which the data were collected through 56 respondents using the saturated sampling. The collected data were analyzed using software Smart PLS. The result of this research shows that Flexible Working Arragement doesn’t effect Employe Loyalty. Employe Engagement and Emotional Intelligence have positive and significant effects to Employe Loyalty